2015
DOI: 10.1002/ejic.201500718
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Boron Complexes of 25‐Oxa­smaragdyrins Containing Axial Silyloxy Groups

Abstract: A series of fluorescent B III complexes of meso-triaryl-substituted 25-oxasmaragdyrins containing axial silyloxy groups were prepared in 80-85 % yields by treating B(OH) 2 complexes of meso-triaryl 25-oxasmaragdyrins with different alkyl/aryl chlorosilanes in toluene in the presence of base at reflux temperature followed by simple column chromatographic purification. The eight axially silyloxy-substituted B III complexes of smaragdyrins were freely soluble in common organic solvents and were characterized by H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The B­(III) complexes of meso -triaryl 25-oxasmaragdyrin containing axial silyloxy groups 288 – 290 were synthesized in high yields by treating B­(OH) 2 –smaragdyrin with different alkyl/aryl chlorosilanes in toluene in the presence of triethylamine at reflux temperature (Scheme ). The X-ray structure of B­(III)–smaragdyrin complex 288 containing trimethylsilyloxy groups revealed that the smaragdyrin macrocycle was almost planar and the −OSiMe 3 groups were oriented in the up and down directions with respect to the macrocycle (Figure b).…”
Section: Smaragdyrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The B­(III) complexes of meso -triaryl 25-oxasmaragdyrin containing axial silyloxy groups 288 – 290 were synthesized in high yields by treating B­(OH) 2 –smaragdyrin with different alkyl/aryl chlorosilanes in toluene in the presence of triethylamine at reflux temperature (Scheme ). The X-ray structure of B­(III)–smaragdyrin complex 288 containing trimethylsilyloxy groups revealed that the smaragdyrin macrocycle was almost planar and the −OSiMe 3 groups were oriented in the up and down directions with respect to the macrocycle (Figure b).…”
Section: Smaragdyrinsmentioning
confidence: 99%
“…5.5 Å diameter sapphyrin core 31 (Figure 10a). This stabilization in the solid state was apparently made possible by the five N−H••• F hydrogen bonds with a bond distance of 2.7 Å (140). The solution-state analysis was further performed with increasing aliquots of fluoride in the CH 3 OH solution.…”
Section: Halide Ionsmentioning
confidence: 99%
“…5,[19][20][21] However, when starting materials of Boron are air-sensitive such as BPh 3 , 22-24 BF 3 (OEt 2 ), [25][26][27][28][29][30] BBr 3 , 31,32 and (Mes) 2 BF (Mes = 2,4,6-Me 3 C 6 H 2 ) 33 the synthesis must be carried out in special conditions due to their high toxicity and reactivity (Scheme 1). For example, it has been reported the synthesis of derived from quinolate, [34][35][36][37][38] smaragdyrins, 39 difluoroboron, 40,41 BODIPYs, [42][43][44] and three-coordinated molecules using Schlenk line, [45][46][47] with reaction time ranging from 2 to 18 hours, and other multi-step synthesis , which takes around 5 days. 48 Chan et al have reported a green synthetic approach of fluorescent organoboron compounds derived from Schiff bases by microwaveassisted synthesis.…”
Section: Synthesis Of Luminescent Organoboron Materialsmentioning
confidence: 99%